Antioxidant Capacity of Ethanolic Extract of Nutmeg (Myristica fragrans) Seeds - Bahri, Syamsul; Merta, I Wayan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Nutmeg is a warm, aromatic spice derived from the seed of the Myristica fragrans evergreen tree, native to Indonesia's Banda Islands. It features a rich, slightly sweet flavor with hints of clove and pepper, commonly used in both baked goods and savory dishes. In extracting secondary metabolites of nutmeg seed, we used 96% ethanol. Antioxidant capacity of the extract was analyzed by DPPH assay (1,1-diphenyl-2-picrylhydrazyl) to analyze antioxidant activity with a UV-Vis spectrophotometer. In this study, the antioxidant capacity of nutmeg seed ethanolic extract was categorized as low, with an IC50 value of 171.95 ppm.